2022
DOI: 10.3390/min12070857
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Serving of DOE and RNN-Based Methods to Optimize and Simulate a Copper Flotation Circuit

Abstract: Prediction of metallurgical responses during the flotation process is extremely vital to increase the process efficiency using a proper modeling approach. In this study, two new variants of the recurrent neural network (RNN) method were used to predict the copper ore flotation indices, i.e., grade and recovery within different operating conditions. The model input parameters including pulp pH and solid content as well as frother and collector dosages were first analysed and then optimized using a two-step fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Figure 7 shows the main effect plots for operating factors considered in the experimental design. Detailed explanations regarding the construction of main effect plots are addressed elsewhere [34,[65][66][67]. According to Figure 7, quartz recovery decreases as the air flow rate increases.…”
Section: Interpretation Of Main and Interaction Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 7 shows the main effect plots for operating factors considered in the experimental design. Detailed explanations regarding the construction of main effect plots are addressed elsewhere [34,[65][66][67]. According to Figure 7, quartz recovery decreases as the air flow rate increases.…”
Section: Interpretation Of Main and Interaction Effectsmentioning
confidence: 99%
“…Coal flotation optimization using modified flotation parameters and combustible recovery in a Jameson cell was investigated by Vapur et al Combustible recovery (%) and ash content (%) were used for the optimization of the Jameson flotation variables, and it was found that d 80 = 0.250 mm particle size, 1/1 vegetable oil acids/kerosene ratio, 20% pulp density, 0.600 L/min wash water rate, and 40 cm downcomer immersion depth could be used to separate coal from ash efficiently [33]. A recent approach to simulate complicated separation techniques uses expert systems such as deep learning [27,[34][35][36][37]. Convolutional neural networks (CNNs) stand out among all simulation techniques [38] and now play an increasingly important role in big data predictive analytics [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies explored the stability of the froth zone under varying flotation conditions and highlighted the significance of the relationship between particle and bubble sizes as critical factors impacting successful collection, froth transport processes, and the flotation rate and efficiency. The third group of papers in this Special Issue delved into modeling and optimizing the flotation process performance utilizing advanced computational tools and algorithms such as the response surface methodology (RSM), GA, ANN, deep learning, and fuzzy systems [10][11][12][13][14]. Some of the studies published in this Special Issue aimed to address the challenges of recovering target elements more effectively using these methods.…”
mentioning
confidence: 99%